Soil erosion projection and response to changed climate and land use and land cover on the Loess Plateau - Biao Zhang; Jialong Guo; Haiyan Fang; Shufang Wu; Hao Feng; Kadambot H.M. Siddique (Agricultural Water Management)
The Grain for Green Project has profoundly altered land use and Land cover (LULC), climate, and soil loss rates on the Loess Plateau over the past few decades. Evaluation and projection of soil erosion with the impacts of climate and LULC are essential for soil erosion control. This study focuses on the Jiuyuangou watershed (JYG), a typical representative of the climate and geographical characteristics of the Loess Plateau. Utilizing the Coupled Model Intercomparison Project Phase 6 (CMIP6) and environmental data, the Revised Universal Soil Loss Equation (RUSLE) coupled with the Future land use simulation (FLUS) model was used to assess soil loss rates for historical periods and various future scenarios. Furthermore, the qualitative and quantitative analysis methods were explored to evaluate the impacts of LULC and climate change on soil erosion. The forest and grass in the JYG increased from 33.4 % in 1995 to 74.1 % in 2020. The soil loss rate significantly decreased, from 64.95 t ha−1·yr−1 in 1995–4.52 t ha−1·yr−1 in 2020. The trend of converting cropland to forest and grass is predicted to continue under different future scenarios. The soil erosion will increase from 2030 to 2050 for different scenarios compared to 2020. The LULC development scenario aiming at ecological protection will effectively curb the increase in soil erosion compared with other scenarios. LULC exerted its influence in various forms across different historical phases. Attribution analysis indicated that the construction of check dams effectively reduced soil erosion from 1995 to 2005, while afforestation from 2005 to 2020 accounted for 64.6 % of the overall contribution. The increase in soil erosion is primarily attributed to more erosive rainfall events and unreasonable allocation of LULC. The correlation between LULC and soil erosion will decrease compared to climate. These findings elucidate the long-term mechanisms of soil erosion changes, emphasizing the urgency of sustainable practices to mitigate soil erosion in the face of environmental challenges.